Ontogenetic instars of Elliptochthonius profundus Norton, 1975 (Acari, Oribatida, Elliptochthoniidae), with remarks on juveniles of the superfamily Parhypochthonioidea - Ermilov, Sergey G.; Bayartogtokh, Badamdorj (Zootaxa, 2022)
The morphology of juvenile instars of the mite Elliptochthonius profundus Norton, 1975 (Oribatida, Elliptochthoniidae) is studied. Comparative characteristics of juveniles of the representative genera in the superfamily Parhypochthonioidea is given based on our own data and available literature sources, and the major characteristics of larvae and nymphs are presented. It can be summarized that the juveniles of parhypochthonioides have the following character states: body trichoid, i.e., the postpedal scissure of gastronotum is clearly developed; body colour whitish or pale yellowish, lacking the strong cuticular sclerotization, where the flesh cuticle is sparsely foveolate or weakly microtuberculate; the juveniles of the different genera are generally similar, but differ from one another in the shape of bothridial seta, number of gastronotic setae, setations of gnathosomal, anogenital and epimeral regions and legs, development of the genital and aggenital plates and peranal segment.